Kombinasi Konsentrasi dan Interval Pemberian Kitosan terhadap Pertumbuhan dan Hasil Kedelai (Glycine max L.) Varietas Grobogan - Rd Budiasih; Linlin Parlinah; Reni Nurhayatini; Suparman; Tria Badriani (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2020)
The continued availability of Chitosan becomes the potential for the presence of Chitosan to be utilized in agriculture, especially to see its influence on soybean growth and yield. The design of the environment is used Complete Random Design, there are seven treatments and repeated 4 times. The combination and interval of Chitosan tested are: A: control; B: 4% chitosan at intervals of 5 days; C: 4% chitosan at intervals of 10 days; D: 4% chitosan at intervals of 15 days; E: 8% chitosan at intervals of 5 days; F: 8% chitosan at 10-day intervals; G: 8% chitosan with 15-day Duncan Test interval of 5% used for advanced tests. Results showed that a combination of concentration and intervals of Chitosan showed an influence on the height of the plant, the number of leaves and the weight of soybean seed Grobogan varieties. The combination of 8% chitosan concentration with 5-day interval is the best result for soy seed weighting per plant which is able to increase the yield by 61.64% when compared to control.